Combinational System of a Truncated Ball Lens and a Hyperbolic Lens for Collimating a Highly Divergent Source - Chen, Lee C.; Low, Andy L. Y.; Chien, Su Fong (Optica Publishing Group, 2004)
We propose the use of a truncated ball lens in a collimating system to transform a spherical wave from a highly divergent source into a plane wave. The proposed scheme, which incorporates a hyperbolic lens, is discussed, and the overall system is found to have a large acceptance angle and to be free of spherical aberration. Diffraction and polarization effects are neglected, as well as skew rays. (C) 2004 Optical Society of America.